Physiotherapy After Anterior Cruciate Ligament Reconstruction – a Literature Review - Karolina Rutkowska-Kogut; Aleksandra Truszczyńska-Baszak; Zuzanna Wrzesień (Rehabilitacja Medyczna)
Introduction: The anterior cruciate ligament (ACL) is the main stabiliser that inhibits excessive anterior translation of the tibia and prevents excessive rotational movements of the knee joint. ACL injuries occur at a frequency of 30 to 78 per 100,000 people a year, leading to instability and impaired function of the knee joint. Continuous development of knowledge on the anatomy and functions of the anterior cruciate ligament, along with the improvement of surgical and physiotherapeutic techniques, allowed for the development of satisfactory modern methods for treating ACL lesions.Objective: The aim of the study is to review literature on modern methods of physiotherapy after the reconstruction of the anterior cruciate ligament.Material and methods: Pubmed, Google Scholar and ScienceDirect scientific databases were searched using a combination of keywords: anterior cruciate ligament, ACL, reconstruction, physiotherapy, protocol. The inclusion criteria were: publication date from the last 10 years and a detailed description of the physiotherapy protocol included.Results: Six publications meeting the inclusion criteria were included in the analysis. Selected physiotherapy protocols consisted of 3 to 5 phases. Phase 1 was focused on reducing pain and swelling in all cases. The purpose of the following phases was to increase the range of motion and to strengthen muscle strength as well as neuromuscular coordination. The final stage consisted of dynamic exercises allowing to prepare for a chosen sports activity.Conclusion: Contemporary protocols for physiotherapy after ACL reconstruction are based on early recovery of range of motion in the knee joint, early increase in load on the operated limb as well as shortening (or excluding) the period of immobilisation and the use of orthoses.